Altered visual repetition suppression in Fragile X Syndrome: New evidence from ERPs and oscillatory activity. Issue 59 (June 2017) - Rigoulot, Simon; Knoth, Inga S.; Lafontaine, Marc-Philippe; Vannasing, Phetsamone; Major, Philippe; Jacquemont, Sébastien; Michaud, Jacques L.; Jerbi, Karim; Lippé, Sarah
Highlights: We investigated alteration of repetition suppression using faces patients suffering from Fragile X Syndrome (FXS). The N170 was not affected by repetition of faces in controls but was altered in FXS patients. Theta band energy was attenuated by repetition in controls but not in patients. This study provides evidence for diminished ERP and oscillatory habituation effects in response to face repetitions in FXS. Abstract: Fragile X Syndrome (FXS) is a neurodevelopmental genetic disorder associated with cognitive and behavioural deficits. In particular, neuronal habituation processes have been shown to be altered in FXS patients. Yet, while such deficits have been primarily explored using auditory stimuli, less is known in the visual modality. Here, we investigated the putative alteration of repetition suppression using faces in FXS patients compared to controls that had the same age distribution. Electroencephalographic (EEG) signals were acquired while participants were presented with 18 different faces, each repeated ten times successively. The repetition suppression effect was probed by comparing the brain responses to the first and second presentation, based on task-evoked event-related potentials (ERP) as well as on task-induced oscillatory activity. We found different patterns of habituation for controls and patients both in ERP and oscillatory power. While the N170 was not affected by face repetition in controls, it was altered in FXS patients. Conversely, while a repetition suppression effect was observed in the theta band (4–8 Hz) over frontal and parieto-occipital areas in controls, it was not seen in FXS patients. These results provide the first evidence for diminished ERP and oscillatory habituation effects in response to face repetitions in FXS. These findings extend previous observations of impairments in learning mechanisms and may be linked to deficits in the maturation processes of synapses caused by the mutation. The present study contributes to bridging the gap between animal models of synaptic plasticity dysfunctions and human research in FXS.